1964
DOI: 10.1111/j.1748-1716.1964.tb02944.x
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Input Impedance and Apparent Phase Velocity in the Human Aorta

Abstract: GABE, I. T., J. KARNELL, I. G. P O R J~ and B. RUDEWALD. The measurement of input impedance and apparent phase velocity in the human aorta. Acta physiol. scand. 1964. 61. 73-84. Measurement of the input impedance in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

1968
1968
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 13 publications
3
13
0
1
Order By: Relevance
“…3). Modulus and phase of impedance in these subjects were similar to those found by others in man (Gabe et al, 1964;Patel et al, 1965;Mills et al, 1970;Nichols et al, 1977;Pepine et al, 1978;Murgo et al, 1978a;Westerhof et al, 1979). Characteristic impedance (the value of impedance modulus about which fluctuations occur) was approximately 600 dyne sec cm" 3 or with aortic diameter AA 100 BCA ported by others for man.…”
Section: The Arterial Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…3). Modulus and phase of impedance in these subjects were similar to those found by others in man (Gabe et al, 1964;Patel et al, 1965;Mills et al, 1970;Nichols et al, 1977;Pepine et al, 1978;Murgo et al, 1978a;Westerhof et al, 1979). Characteristic impedance (the value of impedance modulus about which fluctuations occur) was approximately 600 dyne sec cm" 3 or with aortic diameter AA 100 BCA ported by others for man.…”
Section: The Arterial Modelsupporting
confidence: 88%
“…Studies of vascular impedance and of pulse wave contour in man generally have been interpreted in terms of peripheral wave reflection (Gabe et al, 1964;Mills et al, 1970;Nichols et al, 1977;Pepine et al, 1978), but there is no agreement as to the intensity of wave reflection or the site or sites of reflection. Recent studies (Murgo et al, 1978a(Murgo et al, , 1978bWesterhof et al, 1979) have been interpreted in terms of one apparent reflecting site in the vicinity of the distal aorta, with variable reflection, ranging from strong to minimal, in different patients and under different conditions.…”
mentioning
confidence: 99%
“…The contour of the flow pulse was similar in configuration to that obtained from normal subjects in this laboratory (6, 7) and in others (8,9) with the pressure gradient technique. In the three patients with mitral insufficiency the flow was not abnormally small during the last part of ejection as recently described by Elkins, Morrow, Vasco, and and Braunwald (33).…”
Section: Column 5)supporting
confidence: 58%
“…The technique has been experimentally evaluated in both a flow generator (3) and in the dog aorta (4) and found to yield a valid estimate of phasic flow. The technique has been applied sucessfully in this laboratory (5,6) and by other investigators (7)(8)(9) to measure pulsatile blood pressure and flow in the ascending aorta of the intact human subject. The instrumental techniques, manometric accuracy requirements, and calibration procedures used in our laboratory to obtain valid phasic flow and pressure data in man have been previously described in detail and will only be reviewed briefly (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…'5 A second possibility is that this elevated aortic input impedance represents the result of chronic stimulation of the alpha adrenergic nervous system in addition to sodium retention.3 When vessel wall tension is elevated in isolated arterial segments by alpha catecholamine administration, there is an increase in stiffness of this vascular segment. '6 Gabe et al 17 reported an increase in aortic impedance during norepinephrine infusion. The possibility that the impedance increase is secondary to an overdistended aorta operating over a steeper portion of its distensibility relationship (i.e., pressure-diameter) is excluded by the lack of an increased mean distending pressure in the aorta of the heart failure patients compared to the non-heart failure subjects.…”
Section: Discussionmentioning
confidence: 97%